An elementary equilibrium existence theorem. - Quah, J (Nuffield College (University of Oxford), 2000)
This paper gives a proof of the existence of competitive equilibrium under the added assumption that the excess demand function satises the weak axiom. In this case, a proof using the separating hyperplane theorem, and without using a xed point theorem, is possible.